Analisis Rasio Profitabilitas Dan Kebijakan Dividen Dalam Memprediksi Pertumbuhan Laba Pada Perusahaan Perbankan Yang Terdaftar di BEI Tahun 2016-2019 - Weni Afrilliansyah; Ronny Malavia Mardani; Fahrurrozi Rahman (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
AbstractThis research aims to test the effect of Return On Assets (ROA), Return On Equity Ratio (ROE), Net Profit Margin (NPM), and Dividend Payout Ratio (DPR) on Profit Growth in Banking Companies in 2016-2019. This research uses quantitative research methods. The population used is all banks listed on the Indonesia Stock Exchange (IDX) during the research period. The selection of samples is determined by purposive sampling to obtain as many as 12 companies. The results showed that ROA had a positive and significant effect on profit growth, ROE had a negative and insignificant effect on NPM profit growth had a positive and insignificant effect on profit growth, and DPR had a negative and insignificant effect on profit growth. The results of this study using the t test showed that ROA, ROE, NPM, and DPR partially affected profit growth. The coefficient of determination show that the variables ROA, ROE, NPM, and DPR partially affect the 32.1% Profit Growth. Keywords: Return On Assets (ROA), Return On Equity Ratio (ROE), Net Profit Margin (NPM), and Dividend Payout Ratio (DPR), Profit Growth.